فاعلية نظم المعلومات في إدارة الأزمات - دراسة نظرية- - شاهد, عبد الحكيم; زرقون, محمد (جامعة الوادي - University of Eloued, 2017)
نجاح المنظمات اليوم يكمن في قدرتها على مواكبة التطورات،الأمر الذي يلزم عليها التكيف مع التغيرات البيئية ،التي ينجم عنها الكثير من الأزمات التي تهدد كيانها وإستمراريتها وتطورها،فقدرة المنظمات على رصد التغيرات البيئية يساعدها على التكيف معها،ومنه تصبح طريقة التعامل مع الأزمات أمر هين، ولكي تستطيع المنظمة التعامل مع الأزمات التي تعترضها أصبح لزاما عليها أن تعرف المؤشرات التي تنبئ بها قبل وقوعها والاستعداد لها بما يوفر لها من معلومات كافية ودقيقة ومخططة،تضمن وصولها إلى متخذ القرار في الوقت المناسب،لذلك وجب أن يكون نظام المعلومات قادرا على تزويد كل المستويات الإدارية من معلومات تكون مفيدة مما ينعكس بالإيجاب على إمكانية إدارة المنظمة للازمات التي تواجهها . The success of the organizations today lies in their ability to cope with developments, which requires them to adapt to environmental changes, which result in many crises that threaten their existence, continuity and development. The ability of organizations to monitor environmental changes helps them adapt to them. , And in order for the organization to deal with the crises it faces, it has to identify and prepare the indicators that it predicts before they occur and provide them with sufficient, accurate and planned information to ensure that they reach the decision-maker in a timely manner. Therefore, the information system must be able to The hands of all administrative levels of information to be useful, which is reflected positively on the possibility of the Organization's management of crises faced
Effectiveness of information systems in crisis management - Theory study -
مقال
Keywords: نظم المعلومات، فاعلية نظام المعلومات، إدارة الأزمات; Information Systems, Information System Effectiveness, Crisis Management.